Can central bank communication help to stabilise inflation expectations? - Alexander Jung; Patrick Kühl (European Central Bank (ECB), 2021)
This paper examines whether central bank communication stabilises euro area inflation expectations through the information and news channel. A novelty of the study is its use of data from Google Analytics on ECB website traffic as proxy for visitors' attention to its communication. We conduct several econometric tests with daily data to measure the impact of ECB communication on the information demand of the public and ultimately on inflation expectations. Overall, this study shows that website attention, as captured by search volumes of visitors, influences euro area inflation expectations. We find that increased website attention contributes to narrowing the gap between market-based forecasts and (the mean of) longer-term professional inflation expectations. Our findings add to the theoretical evidence on the existence of an information and news channel.
Keywords: C20; D80; E52; E58; G14; 330; website attention; high-frequency identification; forward guidance; information demand; information and news channel